2014
DOI: 10.1002/ejoc.201403119
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Photostable Energy‐Transfer Pair for “DNA Traffic Lights”

Abstract: A new cyano‐substituted thiazole red derivative as a red emitter and a novel green fluorescent donor dye of the cyanine styryl type were synthesized in good yields. Characterization of their optical properties revealed excellent photostabilities and large apparent Stokes' shifts. Both dyes can be incorporated into oligonucleotides through postsynthetic “click”‐type chemistry and combined in a diagonal arrangement in double‐stranded DNA. As a result, both dyes combine to an energy‐transfer pair in DNA that show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…In order to readout the strand displacement dynamics with acpcPNA not only by conventional fluorescence intensity changes at a single emission wavelength, we followed our concept of wavelength-shifting nucleic acid probes. 44 In order to apply such fluorescence color changes to directly report the dynamics of strand displacements in vitro we synthesized the 14mers PNA1 and PNA2 that carry the blue emitting dye 1 in the middle of the sequence (Fig. 25,43 Moreover, we showed that this concept works also for pairs of fluorescent dyes attached to the 2′-positions in two different DNA strands and yields even better emission color contrasts as readout.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to readout the strand displacement dynamics with acpcPNA not only by conventional fluorescence intensity changes at a single emission wavelength, we followed our concept of wavelength-shifting nucleic acid probes. 44 In order to apply such fluorescence color changes to directly report the dynamics of strand displacements in vitro we synthesized the 14mers PNA1 and PNA2 that carry the blue emitting dye 1 in the middle of the sequence (Fig. 25,43 Moreover, we showed that this concept works also for pairs of fluorescent dyes attached to the 2′-positions in two different DNA strands and yields even better emission color contrasts as readout.…”
Section: Resultsmentioning
confidence: 99%
“…25,43 Moreover, we showed that this concept works also for pairs of fluorescent dyes attached to the 2′-positions in two different DNA strands and yields even better emission color contrasts as readout. 44,45 The dye 1-labeled PNA1 and PNA2 were separately annealed with the unmodified 7mer oligonucleotide counterstrand DNA1 to obtain the starting duplexes for strand displacement experiments. 2).…”
Section: Resultsmentioning
confidence: 99%
“…, A fluorescence color contrast (red/green) of up to 20:1 was achieved together with a large wavelength shift of 140 nm between excitation and emission. Moreover, dyes with significantly enhanced photostability can be combined as 2′‐modifications in a diagonal arrangement similar to the previous base substitutions in DNA and yield derivatives with remarkable wavelength‐shifting fluorescent properties …”
Section: Figurementioning
confidence: 99%
“…The photostabilities of both dyes in the presence of double‐stranded DNA (random sequence, see Supporting Information) under irradiation with a xenon lamp (75 W, 305 nm cut‐off filter) were compared with the fluorescence half‐lives ( t 1/2 ) (Figure ). Compared with thiazole orange ( t 1/2 =32 min) and thiazole red ( t 1/2 =7 min), both the green‐emitting dye ( 1 ) and the red‐emitting dye ( 2 ) showed significantly improved photostability with t 1/2 values of 293 min and 317 min, respectively.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation